Fundamental aerodynamics of the soccer ball - Asai, T.; Seo, K.; Kobayashi, O.; Sakashita, R. (Sports Engineering, 2007)
When the boundary layer of a sports ball undergoes the transition from laminar to turbulent flow, a drag crisis occurs whereby the drag coefficient (Cd) rapidly decreases. However, the aerodynamic properties and boundary-layer dynamics of a soccer ball are not yet well understood. In this study we showed that the critical Reynolds number (Remt) of soccer balls ranged from 2.2 x 105 to 3.0 x 105. Wind-tunnel testing, along with visualisation of the dynamics of the boundary layer and the trailing vortex of a ball in flight, demonstrated that both non-spinning and spinning (curved) balls had low Cd values in the super-critical region. In addition, the Remt values of the soccer balls were lower than those of smooth spheres, ranging from -3.5 x 105 to 4.0 x 105, due to the effects of their panels. This indicated that the aerodynamic properties of a soccer ball were intermediate between those of a smooth ball and a golf ball. In a flow visualisation experiment, the separation point retreated and the Cd decreased in a super-critical regime compared with those in a sub-critical regime, suggesting a phenomenon similar to that observed in other sports balls. With some non-spinning and spinning soccer balls, the wake varied over time. In general, the high-frequency component of an eddy dissipated, while the low-frequency component increased as the downstream vortex increased. The causes of the large-scale fluctuations in the vortex observed in the present study were unclear; however, it is possible that a 'knuckle-ball effect' of the non-rotating ball played a role in this phenomenon.